Synthesis, Characterization and Biological Activity Study for Some New Metals Complexes with (3Z,3'E)-3,3'-(((2E,5E)-hexane-2,5-diylidene)bis(hydrazine-2,1-diylidene))bis(indolin-2-one) - Abd AL_Qadir, Nuha Ayad; Shaalan, Naser Dheyaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Our recent work displays the successful preparation of Schiff_bases that carried out between hexane-2,5-dione and 2 moles of (Z)-3-hydrazineylideneindolin-2-one forming in Schiff-bases-(L), Which in turn allowed combining with each of the next metal ions: (M2+) = Ni, Mn, Zn, Cu and Co forming complexes_ in high stability. The formation of resulting Schiff_ bases (L) is detected spectrally using LC_Mss which gave approximately matching results with theoretical incomes, 1HNMR proves the founding of doublet signal of (2H) for 2NH, FTIR indicates the occurrence of two interfered imine bands and UV-VIS mean is also indecates the formation of ligand. On the other hand, complexes-based-Schiff were characterized using the same spectral means that relied Schiff-bases_(L). Those means gave satisfactory results and proved the distinguishable geometries that suggested. Finally, and according to the antibiotic feature of Schiff-bases and its metal ions we have also examined such character against (-Bacteria and +Bacteria) giving an acceptable inhibition efficiency.